2010
DOI: 10.1111/j.1752-4571.2010.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic vector divergence masks vector‐specific patterns of infection: an example from the marine cycle of Lyme borreliosis

Abstract: Vector organisms are implicated in the transmission of close to a third of all infectious diseases. In many cases, multiple vectors (species or populations) can participate in transmission but may contribute differently to disease ecology and evolution. The presence of cryptic vector populations can be particularly problematic as differences in infection can be difficult to evaluate and may lead to erroneous evolutionary and epidemiological inferences. Here, we combine site-occupancy modeling and molecular ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 76 publications
1
76
0
Order By: Relevance
“…Detailed analyses of tick infections by Bbsl indicated significant differences in local prevalence estimates among different sympatric tick populations (Gómez-Díaz et al, 2010; Table 1). While little variation exists among host groups in terms of the presence of different Bbsl genospecies (Table 1), significant genetic structure is evident if one looks at strain variation within a given genospecies (Table 2).…”
Section: Consequences For Pathogen Circulationmentioning
confidence: 99%
“…Detailed analyses of tick infections by Bbsl indicated significant differences in local prevalence estimates among different sympatric tick populations (Gómez-Díaz et al, 2010; Table 1). While little variation exists among host groups in terms of the presence of different Bbsl genospecies (Table 1), significant genetic structure is evident if one looks at strain variation within a given genospecies (Table 2).…”
Section: Consequences For Pathogen Circulationmentioning
confidence: 99%
“…The strong spatial and temporal structure of I. uriae populations, the range of potential seabird species exploited and the complex interaction between the tick and its vertebrate host may have favoured the evolution of host specialisation in this system (Magalhaes et al 2007). Indeed, several studies have now demonstrated that genetically distinct populations of this tick exploit different sympatric seabird species (McCoy et al 2001(McCoy et al , 2005b and that the presence of these hostassociated races can have an important impact on tick dispersal (McCoy et al 2003) and pathogen transmission (Gómez-Díaz et al 2010). Like most ectoparasites, I. uriae shows only weak independent dispersal abilities and must rely on seabird movements for intercolony dispersal (Danchin 1992, McCoy et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…As I. uriae ticks tend to show restricted host use within colonies (Gómez-Díaz et al, 2010) and king penguins do not frequently change colonies (Weimerskirch et al, 1992), our results suggest that Bbsl is maintained locally and, thus, Bbsl enzootic foci are present in the Southern Hemisphere. RLFP results also suggest that Bbsl DNA detected in king penguins is related to B. garinii, matching an earlier study that found B. garinii in I. uriae from the Crozet Islands (Olsen et al, 1995).…”
Section: Discussionmentioning
confidence: 85%
“…In the marine ecosystem of Bbsl, B. garinii appears to be the main Bbsl species infecting I. uriae, although atypical genospecies such as B. lusitaniae, B. afzelii and B. burgdorferi sensu stricto may also be present (Dietrich et al, 2008;Duneau et al, 2008). Several studies in the literature have reported the detection (by PCR or culture) of Bbsl in I. uriae collected from various seabirds colonies (Olsen et al, 1993(Olsen et al, , 1995Smith et al, 2006;Larsson et al, 2007;Duneau et al, 2008;Comstedt et al, 2009;Gómez-Díaz et al, 2010, and on the presence of anti-Bbsl antibodies in blood samples collected from seabirds of both hemispheres (Gauthier-Clerc et al, 1999;Gylfe et al, 1999;Staszewski et al, 2008;Lobato et al, 2011). However, direct reports on Bbsl detection in seabirds are scarce (Gylfe et al, 1999) and to our knowledge, our study is the first one reporting direct Bbsl detection from seabirds in the Southern Hemisphere.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation